Evaluation of some individual antioxidants in seminal plasma of fertile & infertile men. - Hassan, Hathama Razooki; Ena, Enam J. (Journal of the Faculty of Medicine Baghdad, 2005)
(2000) Summary:(2001) Background: infertility is defined as the inability of a couple to conceive after one year of a regular unprotected intercourse with the same partner. Many factors seem to play a role in male infertility.(2002) Aim: to evaluate the role of some seminal plasma biochemical components in male infertility.(2003) Methods: seminal plasma of 100 infertile men & 25 fertile men were chosen as a subject of this study.(2004) Different biochemical parameters that are related to oxidative stress were measured. These included Glutathione Peroxidase (GSHPX),superoxide dismutase (SOD),cerulopasmin (CP) scavenging activity, albumin & total sulfhydral (T-SH) & its individual parts (protein & non protein binding sulfhydral (PB-SH & NP-SH)).(2005) Results:- a significant decrease in GSHPX activity (P